2021
DOI: 10.3390/nano12010146
|View full text |Cite
|
Sign up to set email alerts
|

Single Step Laser-Induced Deposition of Plasmonic Au, Ag, Pt Mono-, Bi- and Tri-Metallic Nanoparticles

Abstract: Multimetallic plasmonic systems usually have distinct advantages over monometallic nanoparticles due to the peculiarity of the electronic structure appearing in advanced functionality systems, which is of great importance in a variety of applications including catalysis and sensing. Despite several reported techniques, the controllable synthesis of multimetallic plasmonic nanoparticles in soft conditions is still a challenge. Here, mono-, bi- and tri-metallic nanoparticles were successfully obtained as a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This effect can be explained not only by the surface topology modification [ 46 , 47 ], but also by the enhanced absorption of laser radiation by the residual species, which led to more efficient heating and to the reduction of copper ions in the eutectic solvent. This assumption lies in agreement with the considerable widening of the structure, despite the increase in scanning speed ( Figure 2 a,b), and confirms that the main driving force of the process is thermal reduction [ 25 ], in contrast with photoinitiated deposition, using photodegradable precursors [ 51 , 52 ].…”
Section: Resultssupporting
confidence: 84%
“…This effect can be explained not only by the surface topology modification [ 46 , 47 ], but also by the enhanced absorption of laser radiation by the residual species, which led to more efficient heating and to the reduction of copper ions in the eutectic solvent. This assumption lies in agreement with the considerable widening of the structure, despite the increase in scanning speed ( Figure 2 a,b), and confirms that the main driving force of the process is thermal reduction [ 25 ], in contrast with photoinitiated deposition, using photodegradable precursors [ 51 , 52 ].…”
Section: Resultssupporting
confidence: 84%
“…In contrast, for deposition with a mixed solution of silver and platinum precursors, the obtained NPs (~40 nm) were uniformly distributed on the PANI matrix; EDX confirmed the presence of both metals ( Figure 2 c,f). Our previous results on the deposition of multi-metallic nanoparticles by LID revealed the formation of structures representing monometallic crystallites and areas of alloys of the respective metals [ 42 ]; this allowed us to assume the formation of similar AgPt structures.…”
Section: Resultsmentioning
confidence: 95%
“…It was found that LID allows the user to control the coating density, morphology, and composition of the MNPs deposited on the substrate’s surface. To date, various mono-, bi-, and trimetallic nanoparticles (Ag, Au, Pt, Cu, Ru, AgPt, and AgAuPt) have been deposited on 2D and 3D amorphous, crystalline, and polycrystalline substrates [ 35 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metallic NPs formation under action of intense laser irradiation is commonly attributed to the generation of solvated electrons and hydrogen radicals produced during optical breakdown of water-based systems [39,[44][45][46] or another active radical species depending on the composition of the solution. [47,48] However many precursors used for synthesis of NPs have the ability to be directly decomposed by laser even in relatively mild conditions far from the plasma formation as a result of photo- [49][50][51] or thermo-induced processes. [52] Here it can be reasonably assumed, that realization of both mechanisms is possible and contributes to the formation of NPs considering below-threshold pulse energies used for surface irradiation.…”
Section: Formation and Characterization Of Nanoparticle-embedded Si L...mentioning
confidence: 99%